Prevalence of Burnout and Job Satisfaction Among Interventional Radiologists in Saudi Arabia - Almamoon I. Justaniah; Renad M. Aljohani; Lama A. Alzelfawi (The Arab Journal of Interventional Radiology)
Purpose To evaluate the prevalence of burnout and job satisfaction among interventional radiologists (IRs) in Saudi Arabia.